Reporting of T4 Genotype of Acanthamoeba Isolates in Recreational Water Sources of Gilan Province, Northern Iran - Niyyati, Maryam; Nazar, Mahdieh; lasjerdi, Zohreh; Haghighi, Ali; Nazemalhosseini, Ehsan (Novelty in Biomedicine, 2015)
Background: Acanthamoeba spp. is the causative agent of blindness keratitis and fatal encephalaitis. Presence of Acanthamoeba spp. in a wide variety of niches such as different water types can lead to exposure of high risk people such as contact lens wearers. The main aim of the present study was to explore the occurrence of Acanthamoeba genotypes in the recreational water sources using both morphological and molecular approaches in Gilan province, Iran. Materials and Methods: Overall, 50 samples were collected from recreational water sources including man- made and natural waters in Gilan province. Filtration and cultivation of samples was performed using non-nutrient agar. Cloning of Acanthamoeba spp. was done to eliminate bacterial and fungi contamination. PCR amplification and sequencing were performed using genus-specific primer pair. Genotype identification was based on homology analysis of 18S rRNA gene (DF3) of the obtained sequences with the available genes in the gene bank data base. Results: Out of 50 water samples, 15 (30%) were positive for Acanthamoeba trophozoites and cysts according to morphological criteria. Cloning of 13 isolates (26%) was done successfully. Molecular analysis of 13 Acanthamoeba strain revealed that all isolates were belonged to potentially pathogenic T4 genotype. Conclusion: T4 genotype is the main cause of Acanthamoeba-related infections. Presence of Acanthamoeba belonged to T4 genotype in recreational water sources is of concern for high risk people. Alarming sign and education to high risk people is of utmost importance to prevent such infections.